Методичне забезпечення дистанційного курсу "Основи педагогіки" - Твердохлєбова, Наталя Євгеніївна (Мелітопольський державний педагогічний університет, 2006)
Activization of educational activity dominates in the organization of distance learning. Methods, that get peculiarities being caused by remoteness of tutor from group for the coordinated activity of all participants of educational process. It is necessary to pay special attention to interactivity of all compounds of training, directed on participant’s educational intensification activity of training for effective carrying out of educational process in distance learning. First of all, it concerns mastering active and group methods of training, means of communication organization that create conditions where a personality can be active and feel himself/herself a subject of educational activity.
Keywords: дистанційні курси; дистанційне навчання; електронне навчання; основи педагогіки